FOR THE APPLICATION OF STATISTICAL CALCULATION USING STANDARD EMPLOYMENT APPLICATION ANGKATA AGE VISUAL BASIC - Novi Tarmawati; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2004)
Statistics is a scientific method of data collection process, describe the data itself sothat data means. A statistic in every observations are often used by many disciplines,such as is used to determine the circumstances and the development of a region orpopulation in each region, the economy and etc.In an economy of statistical observation that is also often applied in the field of labor,such as to determine the standard age of a worker who is now a very complexproblem often encountered in every field of work. Labor force itself is one of themain part of the National Development and human factors kerjamerupakan Valueaddedproduction that provides for economic activities and to help change thestatistics are done by applying statistical methods that exist and are assisted bysupport tools such as computers that have programs -specific programs andapplications to facilitate overcoming the existing problems.In statistical applications, the writer proposes to use Microsoft Visual Basic 6.0,where authors make four forms. Form input displays the number of classes, the upperlimit of the smallest class, the smallest class bawak limits, class intervals to beincluded in the figures represent sampled data on the form as well as frequency. Inthe form shown the results of all the statistics and the calculation results in a chart,which is in the form charts.To companies that will conduct research on statistical samples must understand thebasics of statistics itself, such as how to operate the existing Windows OperatingSystem have the minimal specifications of Hardware and Software.